1991
DOI: 10.1042/bj2770647
|View full text |Cite
|
Sign up to set email alerts
|

Active-site serine mutants of the Streptomyces albus G β-lactamase

Abstract: By using site-directed mutagenesis, the active-site serine residue of the Streptomyces albus G beta-lactamase was substituted by alanine and cysteine. Both mutant enzymes were produced in Streptomyces lividans and purified to homogeneity. The cysteine beta-lactamase exhibited a substrate-specificity profile distinct from that of the wild-type enzyme, and its kcat./Km values at pH 7 were never higher than 0.1% of that of the serine enzyme. Unlike the wild-type enzyme, the activity of the mutant increased at aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…To investigate, variants of the clinically important OXA‐48 and KPC‐2 SBLs were prepared in which the nucleophilic serine was replaced with a cysteine. Consistent with previous reports on the cysteine variants of SBLs, OXA‐48 S70C ( k cat / K M 0.098±0.017 μ m −1 s −1 with the fluorogenic cephem substrate FC5) was not as catalytically active as the wild‐type enzyme ( k cat / K M 0.36±0.06 μ m −1 s −1 with FC5; Supporting Information, Table S1). However, the impact of this substitution on the enzymatic mechanism of the SBLs has not been previously described.…”
Section: Figuresupporting
confidence: 90%
“…To investigate, variants of the clinically important OXA‐48 and KPC‐2 SBLs were prepared in which the nucleophilic serine was replaced with a cysteine. Consistent with previous reports on the cysteine variants of SBLs, OXA‐48 S70C ( k cat / K M 0.098±0.017 μ m −1 s −1 with the fluorogenic cephem substrate FC5) was not as catalytically active as the wild‐type enzyme ( k cat / K M 0.36±0.06 μ m −1 s −1 with FC5; Supporting Information, Table S1). However, the impact of this substitution on the enzymatic mechanism of the SBLs has not been previously described.…”
Section: Figuresupporting
confidence: 90%
“…Evidence presented indicated that an A/G wobble with a seryl-tRNA at the first position of the codon-anticodon interaction was responsible for a limited amount of mistranslation, resulting in production of a small pool of wildtype serine-containing enzyme. A similar phenomenon has been noted by other authors (15). The data presented here are strongly suggestive of a similar mechanism for production of LPase activity in E. coli IT41 and of the Ts growth and preprotein processing phenotype, although it is likely that mistranslation occurs at a rate higher than 0.1% in this case, as the wild-type levels of LPase in E. coli have been estimated to be in the region of 1,000 molecules per cell (40).…”
Section: Discussionmentioning
confidence: 42%
“…This scenario has been supported by structural analysis of the S70G mutant of TEM-1 (46), and has been observed in the mechanistically-related serine proteases (47). In several cases, it was shown that residual activity is the result of a small sub-population of wild-type enzyme produced through the mistranslation of the mutant codon (43, 48). This is not likely the case for OXA-1 S67G, however, as the nitrocefinase activity we observe displays a different K m compared to that seen with wild-type (49).…”
Section: Discussionmentioning
confidence: 99%